Reimagining Academic Service Management in Higher Education: Transformational Strategies for Organizational Change and Student Success - Mozin, Sri Yulianty; Aneta, Yanti; Nani, Yacob Noho; Tohopi, Rustam (Journal of Governance and Public Policy, 2026)
Existing studies on academic service management in higher education have mainly emphasized digitalization, administrative efficiency, and service quality improvement. Less attention has been paid to how leadership, technological innovation, organizational culture, and human resource development interact as an institutional mechanism for sustaining academic service transformation in Indonesian public universities. This study aims to explain how these four dimensions operate together in transforming academic service governance. A theory-guided qualitative case study was conducted at the State University of Gorontalo, selected as a theoretically relevant case because it has implemented SIAT, e-office, chatbot-based information services, cloud-based archives, and mobile service monitoring. Data were collected through in-depth interviews, participatory observations, and document analysis, and were analyzed using hybrid thematic analysis combining deductive and inductive coding. The findings show that academic service transformation is not driven by technology alone. It emerges through a sequential and mutually reinforcing process in which: visionary leadership generates institutional legitimacy; digital innovation redesigns service routines and improves transparency; collaborative culture facilitates coordination and acceptance; and human resource development sustains implementation through competence, motivation, and service commitment. The study contributes to higher education governance literature by proposing the Integrated Academic Service Transformation Model. The model conceptualizes academic service reform as an institutional change process that links leadership-generated legitimacy, digital service redesign, collaborative institutionalization, and human resource learning to support organizational change and student success.